Can ultrasound parameters predict the diagnostic yield of diuretic renal scintigraphy in pediatric hydronephrosis? - Dheeratama Siripongsatian; Nipaporn Tewattanarat; Nantaporn Wongsurawat; Suwannee Wisanuyotin; Daris Theerakulpisut (PLoS ONE, 2025)
Diuretic renal scintigraphy (DRS) is a valuable imaging tool for distinguishing obstructive from non-obstructive hydronephrosis, especially in pediatric patients, but non-diagnostic results are not uncommon. In this retrospective analytical study, we examined if kidney ultrasound (US) parameters can predict non-diagnostic DRS, and DRS with an obstruction pattern, potentially guiding patient selection to reduce unnecessary radiation exposure. The study included 67 patients (134 kidneys), 1-month to 4-years of age who underwent both DRS and US. Receiver operating characteristic (ROC) curve analysis of US parameters including parenchymal thickness, cortical thickness, medullary pyramidal thickness, anterior-posterior renal pelvic diameter, was done to assess the predictiveness of these parameters for prediction of DRS results. None of the US parameters reliably predicted non-diagnostic DRS results (AUC range: 0.41–0.61). However, these parameters demonstrated good predictiveness for identifying DRS with an obstruction pattern (AUC range: 0.69–0.87), with anterior-posterior renal pelvic diameter showing the highest performance. These findings suggest that while US parameters cannot predict non-diagnostic DRS outcomes, they are effective in identifying obstruction patterns on DRS.